The Salient Features of Twin Language Development - Peyman Rajabi (Journal of Global Pharma Technology, 2017)
Multifarious studies indicated that twin language has some prominent features, evinced from the onset of life, as compared closely with single-born children.The current paper intends to illustrate the characteristics of twin language by taking account the following key issues:The effect of genetic or environmental factors on language acquisition (naturevs. nurture).Mother and other older siblings’ interaction to promote the extent of twin language (nurture).The rate of understanding and misunderstanding of twins’ speech.The phonology quality of twins.The language problems which school-age twins more likely encounter in elementary school.This paper arrives at the conclusion that the growth of language acquisition, within twin children, in some suffers from lack of features of language aspects but in some other areas, the percentage of flaw is rare. This typically requires running some further research to expound the momentous issues of twin language due to generalizingwithout any problem.On genetic factors, linguistic discordant takes place but not in a way that leads to raze the construction of communication .In this respect, postnatal factors play crucial role to hamper to imping later language disorders. This lies on the roles of older siblings or parents, particularly mother, who are cognizant of their duties to pave the way for twins to procure language development with ease. Ascribing phonology deficit solely to twins but not on singletons is unfair and a sheer bias approach.Decoding of twin language sounds baffling in the rudimentary steps of interaction among children even the parents but this problem will be resolved by establishing situations to have more engagement with them. Determining commensurate plans by principles in schools, like social-action games and other cooperative activities pave the ground for the twins not to see merely one sibling on their side but variety of imitations, vocabularies of different social class, use of jargons and all aspects of expressive language.Keywords: Genetic, Environment, Maternal speech, Phonology, Misunderstanding, School-age.